Predicting population‐level risk effects of predation from the responses of individuals. Issue 7 (1st July 2014) - MacLeod, Colin D.; MacLeod, Ross; Learmonth, Jennifer A.; Cresswell, Will; Pierce, Graham J.
Abstract : Fear of predation produces large effects on prey population dynamics through indirect risk effects that can cause even greater impacts than direct predation mortality. As yet, there is no general theoretical framework for predicting when and how these population risk effects will arise in specific prey populations, meaning that there is often little consideration given to the key role predator risk effects can play in understanding conservation and wildlife management challenges. Here, we propose that population predator risk effects can be predicted through an extension of individual risk trade‐off theory and show for the first time that this is the case in a wild vertebrate system. Specifically, we demonstrate that the timing (in specific months of the year), occurrence (at low food availability), cause (reduction in individual energy reserves), and type (starvation mortality) of a population‐level predator risk effect can be successfully predicted from individual responses using a widely applicable theoretical framework (individual‐based risk trade‐off theory). Our results suggest that individual‐based risk trade‐off frameworks could allow a wide range of population‐level predator risk effects to be predicted from existing ecological theory, which would enable risk effects to be more routinely integrated into consideration of population processes and in applied situations such as conservation.